ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015-2017 - Loida Yunita, 15.05.52.0330; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the effect of profitability, asset structure, company size, liquidity and institutional ownership on the capital structure. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling method uses purposive sampling with the research period from 2015 to 2017. The data processed is 200 companies. The testing technique uses multiple linear regression analysis. The results showed that profitability, asset structure, company size and institutional ownership did not affect the capital structure, liquidity had a negative effect on capital structure.